The False Memory and the Effect of Murottal Al-Qur’an - Zulmi Ramdani; Ujam Jaenudin; Nani Nuranisah Djamal; Ari Anggara; Faridah Pertiwi; Iyyah Syamsiyah; Muhammad Luthfi; Puput Juliana; Tri Wisda (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to see the effect of giving the Murottal Al-Qur'an to the decrease subject’s level of false memory. Experimental design with post-test only control group design was used in this study. Participants involved in the study were 60 psychology students in the first semester by using random sampling. Participants grouped into an experimental group and a control group, each consisting of 30 participants. The instrument used was a false memory question comprising of 30 questions been validated by expert judgment at the trial stage. The instrument validation was carried out qualitatively by three lecturers with psychological and measurement backgrounds. Validation results show that there are language and content improvements in the instruments used, and then the authors correct them so that all experts agree that the instrument is suitable for use. Meanwhile, the results of the study show that there is a significant difference between the two groups given treatment and not, where from the score obtained, the experimental group obtained a greater score on filling in the false memory test than the control group. These studies inform that giving Murottal Al-Qur'an can reduce the level of false memory in the subject.